Hazards and Management of Wire Bristle ingestions: A Systematic Review. (30th November 2021) - Miller, Nathaniel; Noller, Michael; Leon, Matthew; Moreh, Yonatan; Watson, Nora L.; Costello, Justin; Hong, Steven
Abstract : Objective: Inadvertently ingested grill brush bristles can lodge in various locations and lead to a variety of injuries. They can also be difficult to identify and remove. Our primary objective was to perform a systematic review of cases reported in the literature, with analysis of trends in clinical presentation and success of diagnostic modalities and treatment approaches. Data Sources: Cases of reported grill brush bristle ingestion reported in PubMed, PubMed Central, and Google Scholar databases through April 30, 2021. Review Methods: Databases were searched for the following terms: ("ingestion" OR "injury" OR "barbeque" OR "BBQ" OR "grill" OR "foreign body" OR "brush" AND "wire" OR "bristle"). Data were collected on patient demographics, clinical presentation, and treatment course. Statistical analysis was performed on characteristics with low risk of confounding. Results: An overall 57 studies involving 91 patients were included. Grill brush bristles presented most commonly in the upper aerodigestive tract (48/91), followed by the abdomen (26/91) and deep neck (17/91). Computed tomography was the most accurate imaging modality for initial diagnosis, identifying 92.8% of bristles. Less invasive or adjunctive techniques such as endoscopy, intraoperative imaging, or minimally invasive surgery may be useful particularly for bristles located in the head and neck given the low rate of success of transoral surgery (66.7%). Conclusion: Although this review of retained bristle may be biased toward complex cases, retained grill brush bristles represent an underrecognized and difficult‐to‐manage hazard. When cases are suspected, clinicians should obtain computed tomography imaging based on presentation and tailor management appropriately.